2005
DOI: 10.1007/s10641-005-2228-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the density and biomass of moray eels (Muraenidae) using a modified visual census method for hole-dwelling reef fauna

Abstract: SynopsisWe developed a modified visual census technique suitable for fairly sedentary, hole-dwelling species and used it to determine the diversity, density, biomass, and habitat use of morays at four sites including fringing, patch, and bank reefs in Barbados, West Indies. The method involved a careful search during two passages over transects by day and by night, noting size and position of morays seen, and using the number of new observations on the second passage to estimate the proportion of morays not se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…First, they can cause physical damage to benthic habitats when they are set, hauled, lost or abandoned (Chiappone et al 2002, Sheridan et al 2003, Mangi & Roberts 2006. Also, traps catch moray eels, which likely serve an important but often underappreciated predatory role in coral reef ecosystems, especially in areas where large groupers and snappers have been overfished (Gilbert et al 2005). Further, escape gaps do not reduce catch of wide-bodied bycatch fish (such as trunkfish (Ostraciidae), and scorpionfish (Scorpaenidae)), nor do they allow escape of the large fish that are disproportionately important to reproductive potential (Birkeland & Dayton 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, they can cause physical damage to benthic habitats when they are set, hauled, lost or abandoned (Chiappone et al 2002, Sheridan et al 2003, Mangi & Roberts 2006. Also, traps catch moray eels, which likely serve an important but often underappreciated predatory role in coral reef ecosystems, especially in areas where large groupers and snappers have been overfished (Gilbert et al 2005). Further, escape gaps do not reduce catch of wide-bodied bycatch fish (such as trunkfish (Ostraciidae), and scorpionfish (Scorpaenidae)), nor do they allow escape of the large fish that are disproportionately important to reproductive potential (Birkeland & Dayton 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While this is now well-established for families such as the Haemulidae and nocturnally active species such as members of the family Muraenidae (Gilbert et al 2005), it has not generally thought to be the case for 'herbivores'. Recent studies have demonstrated that species that can play a significant role in the process of herbivory on coral reefs may not be observed during visual censuses of those same reef habitats (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other less diverse families that also live in shallow marine habitats worldwide include the Chlopsidae, Moringuidae, and Muraenesocidae. Although many marine eels likely live in shallow tropical areas, typically only a few species of muraenid eels (Gilbert et al 2005), the colonial garden eels (Thresher 1984;Smith 1989b), or ophichthids with color patterns mimicking sea snakes (Randall 2005) are commonly observed by divers during the day. Other eels of the Nettastomatidae and some Synaphobranchidae may live primarily over the outer continental shelf or on the upper slope.…”
Section: -1 Taxonomic Groups Of Eelsmentioning
confidence: 99%